2014
DOI: 10.1097/ncq.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Is the Hospital's Magnet Status Linked to HCAHPS Scores?

Abstract: This study identified a significant link between Magnet hospitals and higher HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems) scores across 110 Illinois hospitals. Compared with registered nurse nursing hours per patient-day and registered nurse turnover rate, Magnet status was a stronger contributor to the HCAHPS scores. A moderate to strong, reverse relationship between hospital's percentage of African American patients and HCAHPS scores suggests a need for strengthening culturally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Nurses working in environments characterized by a visible and influential chief nursing officer, nurse participation in clinical and administrative decision-making, interdisciplinary collaboration, and innovative evidencebased care practices are well situated to influence patient outcomes. Mounting evidence supports the association between Magnet recognition and patient outcomes, including lower mortality (Aiken et al, 1994;Evans et al, 2014;Friese et al, 2015;Kutney-Lee et al, 2015;McHugh et al, 2013), lower rates of failure-to-rescue (Kutney-Lee et al, 2015;McHugh et al, 2013), fewer patient falls (Lake, Shang, Klaus, & Dunton, 2010), better nurse-reported quality of care (Kutney-Lee et al, 2015), fewer infections (Barnes et al, 2016), and greater patient satisfaction (Chen, Koren, Munroe, & Yao, 2014;Smith, 2014;Stimpfel et al, 2015).…”
Section: Magnet Hospitalsmentioning
confidence: 99%
“…Nurses working in environments characterized by a visible and influential chief nursing officer, nurse participation in clinical and administrative decision-making, interdisciplinary collaboration, and innovative evidencebased care practices are well situated to influence patient outcomes. Mounting evidence supports the association between Magnet recognition and patient outcomes, including lower mortality (Aiken et al, 1994;Evans et al, 2014;Friese et al, 2015;Kutney-Lee et al, 2015;McHugh et al, 2013), lower rates of failure-to-rescue (Kutney-Lee et al, 2015;McHugh et al, 2013), fewer patient falls (Lake, Shang, Klaus, & Dunton, 2010), better nurse-reported quality of care (Kutney-Lee et al, 2015), fewer infections (Barnes et al, 2016), and greater patient satisfaction (Chen, Koren, Munroe, & Yao, 2014;Smith, 2014;Stimpfel et al, 2015).…”
Section: Magnet Hospitalsmentioning
confidence: 99%
“…This indicates many health care organizations have prioritized the provision of culturally sensitive care to LGBTQ clients. Clients report higher satisfaction of care when it is culturally appropriate; and data support positive relationships between Magnet recognition and higher scores on formal care satisfaction inventories, like Healthcare Consumer Assessment of Healthcare Providers and Systems evaluations (Chen, Koren, Munroe, & Yao, 2014; Zhu, Dy, Wenzel, & Wu, 2018). Providing culturally appropriate care is an essential transcultural nursing concept; and it will be increasingly important in the future as populations within the United States continue to diversify (Enestvedt et al, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Despite HCAHPS survey results being publicly reported, are associated with increased patient satisfaction (Boev, 2012). There is some evidence that Magnet-designated hospitals perform better on HCAHPS than non-Magnet hospitals (Chen, Koren, Munroe, & Yao, 2014;Kidd, 2013), further supporting a potential association between the work environment and patients' perceptions of care, including medication communication.…”
Section: Assessment Of Healthcare Providers and Systems (Hcahps) Hospmentioning
confidence: 99%